Evaluation of the BPJS Patient Admission Administration Service System at Pekanbaru Medical Center Hospital - Ilham, Rahmat; Rohendi, A; Andikarya, R. Oke (Research of Service Administration Health and Sains Healthys, 2025)
Pekanbaru Medical Center Hospital has partnered with BPJS Health since 2014, offering outpatient, inpatient, and emergency services. However, the hospital has not fully met patient expectations, especially regarding the speed and accuracy of administrative services, which has affected its public image. This study aims to analyze the implementation, challenges, and improvement strategies of administrative services for BPJS patients. Conducted in Sail District, Pekanbaru City, this qualitative case study used purposive sampling for BPJS patients and snowball sampling for other stakeholders, including all management levels and BPJS Health representatives. Data analysis involved data reduction, presentation, and conclusion drawing. Findings indicate that while the administrative service system is fairly effective, it faces challenges such as inactive BPJS membership, long registration queues, data mismatches between systems, and limited patient understanding. To enhance service quality, the hospital must optimize digitalization, train administrative personnel, and upgrade support facilities to meet patient needs more effectively.